ANALISIS FONOLOGI DALAM TERJEMAHAN ISTILAH KHUSUS KEBIDANAN PADA BUKU BILINGUAL “ENGLISH FOR MIDWIVES PRACTICAL GUIDANCE FOR ANTENATAL CARE” - I Gusti Ayu Agung Dian Susanthi (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2015)
Abstract This study aims at analyzing the generative phonology in the process of translation on bilingual texbook entitled “English for midwives: Practical Guidance for Antenatal care”. The objective is to find out the description of the phonological process on borrowing and calque translation procedure by using generative phonology approach. There are some theories applied in this study, namely Translation Procedures by Vinay and Darbelnet (in Venuti,2000), the theory of generative phonology by Schane (1973), and the theory of morphoponology by Chaer (2013) The result shows that (i) generally midwifery technical term translation has prominent feature in the vowel /i/. Those words can be seen in the TL. (ii) The sound deletion of the midwifery technical term translation tends to delete the last sound such as: /on/ or /ous/ those sounds are deleted after the appearance of vowel /i/. (iii) from the phonological characterstic point of view, the midwifery technical term translation tends to change the vowel sound, which based on generative phonology can be categorized as the weakening of vowel, for example: /plaster/–[ plester]. (iv) The word /menstrual/ which is translated into [ menstruasi] experiences the strenghten vowel /i/ this occurs because of the deletion of phonem /l/ and the additional sound [ si ] in the Indonesian (TL) translation. (v) In the English-Indonesian translation, it is found the example of word which experience vowel blend. (vi) In the translation of midwifery technical term, it is found some words which experience the monoftongisation process. (vii) The midwifery terms in the Indonesian (TL) translation, it is found that the used of abbreviation terms in the TL. This happens because of the midwife would like to make the communication become easier.(viii) There is also an apokop process in the TL translation Keywords: Translation, Midwifery Technical Terms, Generative Phonology